Current practices in long-term video-EEG monitoring services: A survey among partners of the E-PILEPSY pilot network of reference for refractory epilepsy and epilepsy surgery. (May 2016) - Kobulashvili, Teia; Höfler, Julia; Dobesberger, Judith; Ernst, Florian; Ryvlin, Philippe; Cross, J Helen; Braun, Kees; Dimova, Petia; Francione, Stefano; Hecimovic, Hrvoje; Helmstaedter, Christoph; Kimiskidis, Vasilios K.; et al.
Highlights: Epilepsy monitoring units (EMUs) of the E-PILEPSY network were surveyed. Considerable heterogeneity of practice was demonstrated. Organization and safety standards in EMUs need improvement and harmonization. Abstract: Purpose: The European Union-funded E-PILEPSY network aims to improve awareness of, and accessibility to, epilepsy surgery across Europe. In this study we assessed current clinical practices in epilepsy monitoring units (EMUs) in the participating centers. Method: A 60-item web-based survey was distributed to 25 centers (27 EMUs) of the E-PILEPSY network across 22 European countries. The questionnaire was designed to evaluate the characteristics of EMUs, including organizational aspects, admission, and observation of patients, procedures performed, safety issues, cost, and reimbursement. Results: Complete responses were received from all (100%) EMUs surveyed. Continuous observation of patients was performed in 22 (81%) EMUs during regular working hours, and in 17 EMUs (63%) outside of regular working hours. Fifteen (56%) EMUs requested a signed informed consent before admission. All EMUs performed tapering/withdrawal of antiepileptic drugs, 14 (52%) prior to admission to an EMU. Specific protocols on antiepileptic drugs (AED) tapering were available in four (15%) EMUs. Standardized Operating Procedures (SOP) for the treatment of seizure clusters and status epilepticus were available in 16 (59%). Safety measures implemented by EMUs were: alarm seizure buttons in 21 (78%), restricted patient's ambulation in 19 (70%), guard rails in 16 (59%), and specially designated bathrooms in 7 (26%). Average costs for one inpatient day in EMU ranged between 100 and 2200 Euros. Conclusion: This study shows a considerable diversity in the organization and practice patterns across European epilepsy monitoring units. The collected data may contribute to the development and implementation of evidence-based recommended practices in LTM services across Europe.